Is My Body My Property? - Nawrocka, Marta (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate human body law protection system. The author analyse selected issues related to the human body in order to evaluate it in its legal and ethical perspective. Presenting the topic the author refers to the Convention on Human Rights and Biomedicine and the Convention for the Protection of Human Rights and Dignity of the Human Being.